2021
DOI: 10.3390/su132112127
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis of the Stakeholders Involved in the Dromedary Sector in the Mediterranean Region

Abstract: Marginal arid zones in the south Mediterranean are faced with the dramatic departure of their labor forces through migration. Interest in the capacity of the dromedary species to enhance desert ecosystems and to be a potential lever of economic development of these marginal zones only started to grow in the last two decades. Based on an empirical survey of 179 stakeholders in four Mediterranean countries, we explored the links of the stakeholders in the dromedary sector in two dimensions: horizontal links with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In Tunisia, Salmi et al (2018) stated that 58% of breeders are inheritors and either agro-pastoralists or belong to family livestock households in the governorate of Kebili. Besides, each herd's daily work depends on the breeders' social and cultural organization in their territory (Alary et al, 2021). The studied herds showed that three ecotypes from the Marghrebi breed were identified in the governorate of Kebili, and according to their morphological characteristics, they were ranked by importance to Marzougui, Gueoudi, and Ghiloufi ecotypes (Figure 5).…”
Section: Characterization Of Camel Breedingmentioning
confidence: 99%
See 2 more Smart Citations
“…In Tunisia, Salmi et al (2018) stated that 58% of breeders are inheritors and either agro-pastoralists or belong to family livestock households in the governorate of Kebili. Besides, each herd's daily work depends on the breeders' social and cultural organization in their territory (Alary et al, 2021). The studied herds showed that three ecotypes from the Marghrebi breed were identified in the governorate of Kebili, and according to their morphological characteristics, they were ranked by importance to Marzougui, Gueoudi, and Ghiloufi ecotypes (Figure 5).…”
Section: Characterization Of Camel Breedingmentioning
confidence: 99%
“…6, the butcher could also be the trader. This multiple-hatted actor showed a non-specialization of stakeholders of the camel meat sector and led to confusion of roles (Alary et al, 2021). Hussein et al (2013), in their study on the camel meat value chain in Pakistan, found that butchers have a net margin higher than that of the other stakeholders when they slaughter camels on their own.…”
Section: Butchermentioning
confidence: 99%
See 1 more Smart Citation
“…In arid, semiarid, and desert areas, camel (Camelus dromedarius) livestock plays an essential role in the lives of local populations; it provides milk, meat, hair products, transportation, racing, and tourism. Thus, these activities participate in the circular local economy and offer camel herders a fair and stable income (Alary et al, 2021).…”
Section: Introductionmentioning
confidence: 99%